Ericoid mycorrhizal fungi are common root associates of a Mediterranean ectomycorrhizal plant (Quercus ilex) - Bergero, R; Perotto, S; Girlanda, M; Vidano, G; Luppi, a M (Molecular Ecology, 2000)
Mycorrhiza samples of neighbouring Quercus ilex and Erica arborea plants collected in a postcutting habitat were processed to see whether plants differing in mycorrhizal status harbour the same root endophytes. Three experiments were performed in parallel: (i) isolation, identification and molecular characterization of fungi from surface-sterilized roots of both plant species; (ii) re-inoculation of fungal isolates on axenic E. arborea and Q. ilex seedlings; (iii) direct inoculation of field-collected Q. ilex ectomycorrhizas onto E. arborea seedlings. About 70 and 150 fungal isolates were obtained from roots of Q. ilex and E. arborea, respectively. Among them, Oidiodendron species and five cultural morphotypes of sterile isolates formed typical ericoid mycorrhizas on E. arborea in vitro. Fungi with such mycorrhizal ability were derived from both host plants. Isolates belonging to one of these morphotypes (sd9) also exhibited an unusual pattern of colonization, with an additional extracellular hyphal net. Ericoid mycorrhizas were also readily obtained by direct inoculation of E. arborea seedlings with Q. ilex ectomycorrhizal tips. Polymerase chain–restriction fragment length polymorphism and random amplified polymorphic DNA analyses of the shared sterile morphotypes demonstrate, in the case of sd9, the occurrence of the same genet on the two host plants. These results indicate that ericoid mycorrhizal fungi associate with ectomycorrhizal roots, and the ecological significance of this finding is discussed.
Keywords: DNA; ectomycorrhizas; Erica arborea; ericoid fungi; fungi; Fungi: genetics; Fungi: isolation & purification; Fungi: physiology; Genetic; Mediterranean ecosystem; Mediterranean Region; Molecular Sequence Data; Plant Diseases; Plant Diseases: microbiology; Plant Roots; Plant Roots: microbiology; Polymorphism; Quercus ilex; Restriction Fragment Length; Ribosomal Spacer; Trees; Trees: microbiology